Mewujudkan sistem penjaminan mutu internal berkelanjutan melalui pendampingan audit mutu internal - Dimmera, Bella Ghia; Purnasari, Pebria Dheni; Sadewo, Yosua Damas; Jayanti, Wanty Eka (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2023)
The Internal Quality Assurance System is a reference for universities to better manage and organize higher education, prepare students to compete at the global level, and make a greater contribution to the local community. Bumi Sebalo Management Academy Bengkayang faces challenges in implementing the Internal Quality Assurance System, such as a lack of understanding of the Internal Quality Assurance System concept, limited human resources and infrastructure, low commitment to quality culture, and not yet having a certified internal auditor. The purpose of this community service assistance is to support the implementation of the Internal Quality Assurance System through the second cycle of Internal Quality Audit using a Participatory Action Research approach consisting of the identification/assessment stage, planning, program design, implementation, and monitoring, and evaluation. As a result, Bumi Sebalo Management Academy Bengkayang successfully implemented the control cycle and can continue to the Internal Quality Assurance System improvement cycle. This is evidenced by the support of the Organizing Board, college management, the involvement of the entire academic community, and the preparation of the second cycle Internal Quality Audit report. Internal Quality Audit assistance is very useful in realizing a sustainable Internal Quality Assurance System at Bumi Sebalo Management Academy Bengkayang.